PENGUATAN KOMUNITAS PETERNAK KAMBING MELALUI MANAJEMEN PEMASARAN PADA ROKIR FARM DI NAGARI GADUT KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Yola Marzhanda; Devi Yulia Rahmi (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
In general, this program aims to provide strengthening in the development of goat milk farming businesses in Nagari Gadut in overcoming the problems that occur, while in particular it aims to help goat milk farming producers in the field of product marketing in order to expand market share, through providing information about standards and good quality requirements for goat milk quality. This activity was carried out using observation methods, community strengthening workshops and discussions. The benefit of this program is that goat milk producers can determine the type of marketing used to sell their products to the public, so they can expand the market share of goat milk products. Apart from that, this program also provides information to goat milk producers about an effective and efficient marketing management system. The results of this activity show that there is empowerment in the context of strengthening the Rokir Farm breeder community and also seeing the natural potential that exists in Nagari Gadut, holding discussions that add insight that is beneficial for both breeders and students. Rokir Farm livestock in collaboration with the MBKM matching fund has been implemented well, with many supporting programs, one of which is strengthening the Rokir Farm breeder community, we hope that the knowledge provided can be useful for all Rokir Farm breeders and can also develop this knowledge to be even better. than before, and the pasteurization equipment located at Rokir Farm can now be used as well as possible by Rokir Farm farmers.